2009
DOI: 10.1111/j.1552-6569.2009.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Outcome of Microvascular Decompression for Trigeminal Neuralgia Using Magnetic Resonance Tomographic Angiography

Abstract: This study suggests that the curative rate of TN following MVD is higher in the MRTA-positive group. Venous compression and no neurovascular contact that were negative on MRTA image are poor prognostic factors for surgical outcome of TN. Thus, preoperative MRTA serves as a useful tool in patient selection and outcome prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…No randomized controlled trials (RCTs) were identified. Fifteen studies were found investigating the accuracy of preoperative imaging examination to predict the presence of NVC [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. All studies compared the preoperative imaging analysis with surgical data.…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No randomized controlled trials (RCTs) were identified. Fifteen studies were found investigating the accuracy of preoperative imaging examination to predict the presence of NVC [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. All studies compared the preoperative imaging analysis with surgical data.…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
“…All studies compared the preoperative imaging analysis with surgical data. Nine studies were performed using a 1.5-T MR scanner [34,36,38,[40][41][42][43]45,46], six with a 3-T scanner [35,37,39,44,47,48], five studies applied an imaging protocol with only 3D TOF-MRA [34,37,40,43,45]; five with a combination of 3D T2-weighted and 3D TOF-MRA [36,38,39,42,46]; two with a combination of 3D T2-weighted, 3D TOF-MRA and 3D T1-Gad [41,48]; two with a combination of 3D TOF-MRA and 3D T1-Gad [35,47]; and one study with a combination of 3D T2-weighted and 3D fluid-attenuated inversion recovery (FLAIR) [44]. The sensitivity and the specificity of the imaging protocol in detecting NVC varied, respectively, from 67% to 100% and from 50% to 100%.…”
Section: Search Strategy and Resultsmentioning
confidence: 99%
“…1 Patients with little or no neurovascular conflict were less likely to experience pain relief after MVD compared with patients with advanced-grade neurovascular conflict; these results corroborate previous reports from preoperative imaging and intraoperative findings. 4,[9][10][11][12][13][14] In these patients, other etiologic considerations, including pathology in or near the trigeminal root ganglion, may be in play 1,24 and an initial trial with rhizotomy of the trigeminal ganglion could be a rational alternative to MVD, especially if the patient is not an ideal surgical candidate. 1,12 Most higher grade neurovascular conflict was found between 3 and 6 mm from the surface of the pons, corresponding to the location of the root entry zone, in line with findings in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, more severe neurovascular conflict (eg, resulting in deformity or displacement of the nerve) is commonly seen in patients with TN, but not in patients without TN. 4,6,7 Moreover, both the presence and severity of trigeminal nerve root compression have been shown intraoperatively 4,[8][9][10] and by imaging [11][12][13] to be predictive of favorable outcomes after microvascular decompression (MVD). Thus, from these studies, the concept emerges that it is the degree of compression of the CN V root, rather than simply whether there is any neurovascular contact, that is most predictive of symptoms of TN and favorable outcomes after MVD.…”
mentioning
confidence: 99%
“…Sindou and colleagues 5 found no relationship between the location of neurovascular conflict and outcome after surgery, and other investigators have detected neurovascular conflict in the setting of TGN due to venous contact distally along the nerve root near the porus trigeminus. 15 The superior cerebellar artery is the artery most commonly found to contact the trigeminal root, followed by the anterior inferior cerebellar artery, 9,16 and rarely a tortuous basilar artery may come into contact with the nerve root 16 (see Fig. 4B).…”
Section: Imaging Of Neurovascular Contactmentioning
confidence: 98%